The Use of Active Methods for Teaching Mathematics to Students of Economy - Marina Alekseevna Ekimova (Сибирское юридическое обозрение, 2011)
The article examines interdisciplinary approach to teaching mathematics and active methods applied in teaching such as case method and project based learning which are traditionally used in economic education.